Room-temperature-curing water-based ceramic-based heavy anti-corrosion coating

The amorphous phosphate complex salt and flexible polymer coating formed by the reaction of components A and B solves the environmental hazards and brittleness problems of traditional coatings and achieves efficient metal corrosion protection, especially in harsh environments.

CN120795666APending Publication Date: 2025-10-17WINSIN MATERIALS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511125158.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Traditional anti-corrosion coatings contain volatile organic compounds that are harmful to the environment and health. In addition, inorganic coatings are brittle, have limited applications, lack flexibility, and are difficult to meet modern anti-corrosion needs.

Method used

A room temperature curing water-based porcelain-based heavy-duty anti-corrosion coating composed of two components A and B is used. The main film-forming substance is an amorphous phosphate complex salt formed by the reaction of dihydrogen phosphate and metal hydroxide or oxide. It is combined with isocyanate oligomers and amino oligomers to form a flexible polymer coating, providing rust-resistant coating function.

Benefits of technology

The prepared coating has excellent salt spray resistance, water resistance, and condensation resistance, providing efficient protection for metal substrates, especially in high humidity, high salt spray environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a room-temperature curing water-based ceramic-based heavy-duty coating, and belongs to the field of anticorrosive coatings. The coating is composed of a component A and a component B, and is characterized in that the component A is composed of an isocyanate group-containing oligomer, dihydric phosphate, phosphate, phosphoric acid, a pigment filler, water and an auxiliary agent; and the component B is composed of an amino-containing oligomer, an oxide, a hydroxide, a pigment filler, water, a pH value regulator and an auxiliary agent. According to the component A and the component B, dihydric phosphate, phosphoric acid and metal hydroxides or oxides are subjected to an acid-base reaction to form amorphous phosphate double salt which serves as a main film forming substance of a coating, the metal hydroxides and oxides are excessive, and the residual metal hydroxides or metal oxides and pigments and fillers form pigments and fillers of the coating. And a heavy anti-corrosion coating system is jointly constructed. The prepared coating has excellent salt mist resistance, water resistance, brine resistance, condensation resistance and the like, and has an excellent protection function on a metal base material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to anticorrosive coatings, in particular to a room temperature curing waterborne porcelain-based heavy-duty anticorrosive coating. BACKGROUND

[0002] The global economic loss caused by metal corrosion is as high as 3.5 trillion US dollars per year, accounting for about 3.4% of the global GDP (2021 data). This huge loss widely affects infrastructure, industrial equipment and construction fields, not only bringing direct repair and replacement costs, but also leading to productivity decline and environmental damage, threatening economic stability and sustainable development. However, through effective corrosion protection measures, up to 35% of costs, about 875 billion US dollars, can be saved. The importance of corrosion protection technology cannot be ignored, it is not only a key means to reduce economic losses, but also a necessary measure to ensure infrastructure safety and environmental sustainable development. To cope with this global challenge, countries should strengthen cooperation, promote best practices and improve the application of corrosion protection technology to achieve a win-win of economic benefits and social value.

[0003] Traditional corrosion protection coatings are mainly made of organic synthetic resins such as epoxy resin, polyester, polypropylene and other polymers as the main film-forming material. The prepared corrosion protection coatings also have certain volatile organic compounds (VOC), which can cause harm to the environment and users' health. Moreover, these organic coatings have flammable and combustible properties, which pose certain use risks. Currently, there are also inorganic coatings mainly including silicate coatings and phosphate coatings, but inorganic coatings have certain brittleness, which limits their application. Therefore, developing a heavy-duty anticorrosive coating with convenient use, certain flexibility, low VOC or no VOC is the main trend of the development of world coatings. SUMMARY

[0004] The purpose of the present application is to provide a room temperature curing waterborne porcelain-based heavy-duty anticorrosive coating to solve the problems of certain hazards and application limitations of traditional anticorrosive coatings.

[0005] Technical solution: A room temperature curing water-based porcelain-based heavy-duty anticorrosive coating is composed of A and B two components, characterized in that the A component is composed of oligomer containing isocyanate group, dihydrogen phosphate, phosphate, phosphoric acid, pigment and filler, water and additives; the B component is composed of oligomer containing amino group, oxide, hydroxide, pigment and filler, water, pH regulator and additives. The dihydrogen phosphate and phosphoric acid and metal hydroxide or oxide form amorphous double salt of phosphoric acid as the main film-forming material of the coating through acid-base reaction, wherein the metal hydroxide and oxide are in excess, and the residual metal hydroxide or metal oxide and pigment and filler constitute the pigment and filler of the coating, which together build the heavy-duty anticorrosive coating system. In addition, the A component can react with the metal surface while reacting with the B component, and the A component can react with the metal to form a dense alloy phosphating layer, and if there is a small amount of micro-rust on the metal surface, it can also react with the A component to form a dense alloy conversion layer. This feature provides the function of painting with rust for the coating. The dihydrogen phosphate in the A component is represented by A (H2PO4) m ·nH2O, the hydroxide in the B component is represented by B (OH) 2m , or the oxide is represented by B m O 2m . After mixing of the A and B components, the reaction occurs to generate amorphous double salt of phosphoric acid, which becomes one of the main film-forming materials of the coating, and the isocyanate group-containing oligomer and the amino group-containing oligomer perform expansion reaction to form flexible polymer to provide good flexibility for the coating.

[0006] A (H2PO4) m ·nH2O+B (OH) 2m +xH2O = A (BPO4) m ·(n+m+x)H2O

[0007] A (H2PO4) m ·nH2O+B m O 2m +xH2O = A (BPO4) m ·(n+m+x)H2O

[0008] Preferably, the A component is composed of the following substances in percentage by weight: isocyanate group-containing oligomer 5-30%, phosphate 25-55%, phosphoric acid 0.1-15%, pigment and filler 1-30%, water 20-40%, and additives 0.01-5%;

[0009] Among them, the isocyanate group-containing oligomer is selected from at least one of hexamethylene diisocyanate trimer, isophorone diisocyanate trimer, and hydrogenated diphenyl methane diisocyanate trimer;

[0010] The phosphate is selected from at least one of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, aluminum dihydrogen phosphate, magnesium dihydrogen phosphate, calcium dihydrogen phosphate, and potassium dihydrogen phosphate;

[0011] The dihydrogen phosphate has a particle size less than 325 mesh, and is a main film-forming substance. When A and B are mixed, the dihydrogen phosphate reacts with the metal hydroxide or oxide and water to form an amorphous double phosphate;

[0012] The phosphoric acid is commercially available concentrated phosphoric acid;

[0013] The pigment and filler is selected from at least one of kaolin, amorphous silica, alumina, and carbon black;

[0014] The water is deionized water;

[0015] The auxiliary agent is selected from at least one of xanthan gum, diutan gum, tamarind gum, Wrayl gum, hydroxypropyl cellulose, and polyacrylamide.

[0016] Preferably, the pH value of the A component is 1.2-5.5, and more preferably, the pH value is 2.0-3.5; the viscosity is 3000-9000 cp, and more preferably, the viscosity is 4000-7000 cp.

[0017] Preferably, the preparation method of the A component is as follows: deionized water, dihydrogen phosphate, pigment and filler, and auxiliary agent are sequentially added into a reactor, and after being uniformly stirred, the materials are ground to a fineness less than 50 μm by using a grinding device, phosphoric acid is added into the materials, and stirring reaction is performed for not less than 30 min. Filtration and packaging are performed, and before use, the above-mentioned substances are mixed with isocyanate-based oligomers according to a formula amount to obtain a coating A component. The coating A component must be used within 4 h after mixing.

[0018] Preferably, the B component is composed of the following substances according to weight percentage: amino-containing oligomer 5-25%, oxide or hydroxide 25-50%, pigment and filler 1-30%, water 20-40%, pH value adjusting agent 0.01-10%, and auxiliary agent 0.01-3%;

[0019] The amino-containing oligomer is selected from at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, 2-methylimidazole, imidazole, aniline-formaldehyde methylene dianiline, toluene diamine, N-(2-aminoethyl)piperazine, and 4,4'-diaminodiphenyl methane;

[0020] The oxide is a metal oxide, and is selected from at least one of magnesium oxide, iron oxide, aluminum oxide, zinc oxide, calcium oxide, cerium oxide, and zirconium oxide;

[0021] The hydroxide is a metal hydroxide, and is selected from at least one of magnesium hydroxide, aluminum hydroxide, iron hydroxide, zinc hydroxide, calcium hydroxide, cerium hydroxide, and zirconium hydroxide;

[0022] The color filler is selected from at least one of titanium white, talcum powder, wollastonite, silica powder, amorphous silica, iron black, iron yellow, iron red, iron blue, copper-chromium black, copper-iron black, phthalocyanine blue, phthalocyanine green, and carbon black;

[0023] The water is deionized water;

[0024] The auxiliary agent is selected from at least one of sodium citrate, potassium citrate, triethanolamine, boric acid, KH-560, KH-550, potassium acetate, sodium acetate, sodium lignosulfonate, potassium lignosulfonate, potassium oxalate, and sodium oxalate;

[0025] The pH value regulator is selected from at least one of tri-potassium phosphate, di-potassium hydrogen phosphate, tri-sodium phosphate, and di-sodium hydrogen phosphate.

[0026] Preferably, the pH value of the B component is 9.0-13.5, and more preferably, the value is 11-13.2; the viscosity is 3000-9000 cp, and more preferably, the viscosity is 4000-7000 cp.

[0027] Preferably, the preparation method of the B component is as follows: the deionized water, the oligomer containing amino groups, the pH value regulator, the hydroxide or oxide, the color filler, and the auxiliary agent are sequentially added into a container, and are high-speed dispersed or ground, and are filtered and packaged after testing that the fineness is less than 50 microns.

[0028] The A and B components are sprayed by using a two-component spraying device, the spraying device comprises a static mixer, the A and B components are sprayed on the surface of a substrate to form a coating layer after being mixed by the static mixer through pipelines.

[0029] Beneficial effects: the coating prepared by the application has excellent salt mist resistance, water resistance, salt water resistance, and condensation resistance, and has excellent protection function on metal substrates, especially has better protection function on metals in high-humidity and high-salt-mist environments. DETAILED DESCRIPTION

[0030] In order to make the technical scheme of the application clearer, the application is further described in detail below in combination with specific examples.

[0031] Example 1:

[0032] A room temperature curing water-based porcelain-based heavy-duty anticorrosive coating, comprising:

[0033] An A component composed of hexamethylene diisocyanate trimer 5%, potassium dihydrogen phosphate 25%, commercially available concentrated phosphoric acid 0.1%, kaolin 1%, deionized water 20%, and xanthan gum 0.01%.

[0034] Deionized water, potassium dihydrogen phosphate, kaolin, xanthan gum were added into the reactor in turn, after stirring evenly, the material was ground to fineness less than 50μm by grinding facilities, commercial concentrated phosphoric acid was added into the material, and the stirring reaction was not less than 30min. Filtration and packaging, before use, the above-mentioned substance was mixed with hexamethylene diisocyanate trimer according to the formula amount to form the coating A component, the pH value was 3.5, and the viscosity was 4000cp.

[0035] The B component was composed of ethylenediamine 5%, magnesium oxide 25%, titanium white 1%, deionized water 20%, potassium phosphate 0.01%, and sodium citrate 0.01%.

[0036] Deionized water, ethylenediamine, potassium phosphate, magnesium oxide, titanium white, sodium citrate were added into the container in turn, and were dispersed or ground at high speed, and then were filtered and packaged after the fineness was tested to be less than 50μm to obtain the B component, the pH value was 11, and the viscosity was 4000cp.

[0037] 20.0g of the A component and 20.0g of the B component were respectively weighed, and were mixed under stirring to form a coating sample 1, the coating sample 1 after reaction was soaked in 100.0g of 80℃ water for 1h, and the pH value was tested to be 6.5 after the cold zone was cooled to room temperature.

[0038] Example 2:

[0039] A room temperature curing water-based porcelain-based heavy-duty anticorrosive coating, comprising:

[0040] The A component was composed of isophorone diisocyanate trimer 10%, ammonium dihydrogen phosphate 30%, commercial concentrated phosphoric acid 3%, amorphous silicon dioxide 12%, deionized water 25%, and diutan gum 0.8%.

[0041] Deionized water, ammonium dihydrogen phosphate, amorphous silicon dioxide, diutan gum were added into the reactor in turn, after stirring evenly, the material was ground to fineness less than 50μm by grinding facilities, commercial concentrated phosphoric acid was added into the material, and the stirring reaction was not less than 30min. Filtration and packaging, before use, the above-mentioned substance was mixed with isophorone diisocyanate trimer according to the formula amount to form the coating A component, the pH value was 3.0, and the viscosity was 4210cp.

[0042] The B component was composed of diethylenetriamine 12%, magnesium hydroxide 30%, talcum powder 8%, deionized water 25%, potassium phosphate dibasic 1%, and triethanolamine 0.3%.

[0043] Deionized water, diethylenetriamine, potassium phosphate dibasic, magnesium hydroxide, talcum powder, triethanolamine were added into the container in turn, and were dispersed or ground at high speed, and then were filtered and packaged after the fineness was tested to be less than 50μm to obtain the B component, the pH value was 11.2, and the viscosity was 4721cp.

[0044] Take 20.0g of A component and 20.0g of B component respectively, mix them thoroughly under stirring to form coating sample 2, immerse the reacted coating sample 2 in 100.0g of 80℃ water for 1h, and test the pH value at room temperature, which is 6.7.

[0045] Example 3:

[0046] A room temperature curing waterborne porcelain-based heavy-duty anticorrosive coating, comprising:

[0047] An A component composed of hydrogenated diphenylmethane diisocyanate trimer 15%, calcium dihydrogen phosphate 33%, commercially available concentrated phosphoric acid 8%, aluminum oxide 17%, deionized water 28%, and tamarind gum 1.2%.

[0048] Add deionized water, calcium dihydrogen phosphate, aluminum oxide, and tamarind gum into a reactor in sequence, grind the materials to a fineness of less than 50μm using a grinding facility after uniform stirring, add commercially available concentrated phosphoric acid to the materials, and stir for not less than 30min. Filter and package, and mix the above-mentioned substances with isohydrazine diphenylmethane diisocyanate trimer according to the formula amount before use to obtain a coating A component, with a pH value of 2.8 and a viscosity of 5127cp.

[0049] A B component composed of 2-methylimidazole 12%, zinc oxide 30%, silicon powder 8%, deionized water 25%, trisodium phosphate 1%, and boric acid 0.3%.

[0050] Add deionized water, 2-methylimidazole, trisodium phosphate, zinc oxide, silicon powder, and triboric acid into a container in sequence, disperse or grind at high speed, filter and package after testing the fineness of less than 50μm to obtain a B component, with a pH value of 11.7 and a viscosity of 5530cp.

[0051] Take 20.0g of A component and 20.0g of B component respectively, mix them thoroughly under stirring to form coating sample 3, immerse the reacted coating sample 3 in 100.0g of 80℃ water for 1h, and test the pH value at room temperature, which is 7.4.

[0052] Example 4:

[0053] A room temperature curing waterborne porcelain-based heavy-duty anticorrosive coating, comprising:

[0054] An A component composed of hexamethylene diisocyanate trimer and hydrogenated diphenylmethane diisocyanate trimer 26%, potassium diphosphine 47%, commercially available concentrated phosphoric acid 12%, carbon black 28%, deionized water 33%, and hydroxypropyl cellulose 3.1%.

[0055] Deionized water, potassium dihydrogen phosphate, carbon black, hydroxypropyl cellulose were added into the reactor in turn, after stirring evenly, the materials were ground to fineness less than 50 μm by grinding facilities, commercial concentrated phosphoric acid was added into the materials, and the stirring reaction was not less than 30 min. Filtration and packaging, before use, the above-mentioned substances were mixed with hexamethylene diisocyanate trimer and hydrogenated diphenyl methane diisocyanate trimer according to the formulation amount to form a coating A component, the pH value was 2.3, and the viscosity was 6531 cp.

[0056] The B component was prepared from N-(2-aminoethyl)piperazine 21%, iron hydroxide 40%, phthalocyanine blue 17%, deionized water 31%, trisodium phosphate and di-potassium hydrogen phosphate 6%, and KH-550 1.5%.

[0057] Deionized water, N-(2-aminoethyl)piperazine, trisodium phosphate and di-potassium hydrogen phosphate, iron hydroxide, phthalocyanine blue, and KH-550 were added into a container in turn, and were dispersed or ground at high speed. After the fineness of the mixture was tested to be less than 50 μm, the mixture was filtered and packaged to obtain the B component, the pH value was 12.3, and the viscosity was 6473 cp.

[0058] 20.0 g of the A component and 20.0 g of the B component were respectively weighed, and were mixed under stirring to form a coating sample 4. The coating sample 4 after the reaction was immersed in 100.0 g of water at 80 ℃ for 1 h, and the pH value was tested to be 7.9 after the cold zone was cooled to room temperature.

[0059] Example 5:

[0060] A room temperature curing water-based porcelain-based heavy-duty anticorrosive coating, comprising:

[0061] The A component was prepared from hexamethylene diisocyanate trimer and isophorone diisocyanate trimer 30%, aluminum dihydrogen phosphate 55%, commercial concentrated phosphoric acid 15%, amorphous silicon dioxide and carbon black 30%, deionized water 40%, and polyacrylamide 5%.

[0062] Deionized water, aluminum dihydrogen phosphate, amorphous silicon dioxide and carbon black, and polyacrylamide were added into the reactor in turn, after stirring evenly, the materials were ground to fineness less than 50 μm by grinding facilities, commercial concentrated phosphoric acid was added into the materials, and the stirring reaction was not less than 30 min. Filtration and packaging, before use, the above-mentioned substances were mixed with hexamethylene diisocyanate trimer and isophorone diisocyanate trimer according to the formulation amount to form a coating A component, the pH value was 2.1, and the viscosity was 6929 cp.

[0063] The B component was prepared from 4,4'-diaminodiphenyl methane 25%, cerium oxide 50%, copper chromium black 30%, deionized water 40%, trisodium phosphate and tripotassium phosphate 10%, and sodium lignosulfonate 3%.

[0064] Deionized water, 4,4'-diaminodiphenyl methane, trisodium phosphate and tripotassium phosphate, cerium oxide, copper chromium black, sodium lignosulfonate were added into a container in turn, and dispersed or ground at high speed. After the fineness of less than 50 microns was tested, the B component was obtained by filtering and packaging. The pH value was 13.0, and the viscosity was 6973 cp.

[0065] 20.0 g of the A component and 20.0 g of the B component were weighed respectively, and mixed under stirring to form a coating sample 5. The coating sample 5 after reaction was immersed in 100.0 g of water at 80°C for 1 h, and the pH value was tested at room temperature. The cold zone was tested to be 8.4.

[0066] The coating samples 1-5 were tested as follows:

[0067] The flexibility was passed according to GB / T 1731 with a bending of 5 mm.

[0068] The adhesion was tested according to GB / T5210, and the adhesion was not less than 3 MPa.

[0069] The abrasion resistance was tested according to the GB / T1768 Taber abrasion tester (CS-17 abrasion-resistant rubber wheel, 1 kg 1000 revolutions) standard, and the test result was less than 50 mg.

[0070] The water resistance was tested according to GB / T30648.2, and the coating was intact after 2000 h of water resistance.

[0071] The salt water resistance was tested according to GB / T30648.1, and the coating was intact after 2000 h of 5% sodium chloride salt water resistance.

[0072] The continuous condensation resistance was tested according to GB / T 13893, and the coating was intact after 2000 h.

[0073] The pencil hardness was tested according to GB 6739, and the Mitsubishi pencil was 9H.

[0074] The salt spray resistance was tested according to GB / T10125, and the neutral salt spray resistance time was not less than 5000 h.

[0075] According to the test results above, the coating prepared by the present application has excellent salt spray resistance, water resistance, salt water resistance, condensation resistance and other properties, and has excellent protection function for metal substrates.

[0076] The above embodiments only express several implementation manners of the present application, and the description is more specific and detailed, but it should not be understood as a limitation on the patent scope of the present application. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, several modifications and improvements can be made, which are all within the protection scope of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims.

Claims

1. A room temperature curing water-based porcelain-based heavy-duty anti-corrosion coating, consisting of two components A and B, characterized in that: Component A consists of oligomers containing isocyanate groups, phosphates, phosphoric acid, pigments and fillers, water, and additives; component B consists of oligomers containing amino groups, oxides, hydroxides, pigments and fillers, water, pH regulators, and additives.

2. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 1, characterized in that: Component A is composed of the following substances by weight: 5-30% isocyanate-containing oligomer, 25-55% phosphate, 0.1-15% phosphoric acid, 1-30% pigment and filler, 20-40% water, and 0.01-5% additive; Wherein, the isocyanate group-containing oligomer is selected from at least one of hexamethylene diisocyanate trimer, isophorone diisocyanate trimer, and hydrogenated diphenylmethane diisocyanate trimer; The phosphate is selected from at least one of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, aluminum dihydrogen phosphate, magnesium dihydrogen phosphate, calcium dihydrogen phosphate, and potassium pentahydrogen diphosphate; The particle size of dihydrogen phosphate is less than 325 mesh and is the main film-forming substance. When A and B are mixed, dihydrogen phosphate reacts with metal hydroxide or oxide and water to form an amorphous phosphate complex salt; Phosphoric acid was commercial concentrated phosphoric acid; The pigment and filler is selected from at least one of kaolin, amorphous silica, alumina and carbon black; Water is deionized water; The auxiliary agent is selected from at least one of xanthan gum, diutan gum, tamarind gum, Brunei gum, hydroxypropyl cellulose and polyacrylamide.

3. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 2, characterized in that: The pH value of component A is 1.2~5.5, and the viscosity is 3000cp~9000cp.

4. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 3, characterized in that: Component A is prepared by sequentially adding deionized water, dihydrogen phosphate, pigments, fillers, and additives to a reactor, stirring thoroughly, and then grinding the mixture to a fineness of less than 50 μm using a grinding machine. Phosphoric acid is then added to the mixture, and the mixture is stirred and reacted for at least 30 minutes. Filter and package the mixture. Before use, thoroughly mix the above substances with an isocyanate oligomer according to the formulated amount to prepare the coating component A.

5. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 1, characterized in that: Component B is composed of the following substances by weight: 5-25% oligomer containing amino group, 25-50% oxide or hydroxide, 1-30% pigment and filler, 20-40% water, 0.01-10% pH adjuster, and 0.01-3% additive. The oligomer containing an amino group is selected from at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, 2-methylimidazole, imidazole, aniline-formaldehyde methylenedianiline, toluenediamine, N-(2-aminoethyl)piperazine, and 4,4'-diaminodiphenylmethane; The oxide is a metal oxide selected from at least one of magnesium oxide, iron oxide, aluminum oxide, zinc oxide, calcium oxide, cerium oxide, and zirconium oxide; The hydroxide is a metal hydroxide selected from at least one of magnesium hydroxide, aluminum hydroxide, iron hydroxide, zinc hydroxide, calcium hydroxide, cerium hydroxide, and zirconium hydroxide; The pigment or filler is selected from at least one of titanium dioxide, talc, wollastonite, silica powder, amorphous silicon dioxide, iron black, iron yellow, iron red, iron blue, copper chrome black, copper iron black, phthalocyanine blue, phthalocyanine green, and carbon black; Water is deionized water; The auxiliary agent is selected from at least one of sodium citrate, potassium citrate, triethanolamine, boric acid, KH-560, KH-550, potassium acetate, sodium acetate, sodium lignin sulfonate, potassium lignin sulfonate, potassium oxalate, and sodium oxalate; The pH regulator is selected from at least one of tripotassium phosphate, dipotassium hydrogen phosphate, trisodium phosphate, and disodium hydrogen phosphate.

6. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 5, characterized in that: The pH value of component B is 9.0~13.5, and the viscosity is 3000cp~9000cp.

7. The room temperature curing water-based porcelain-based heavy-duty anticorrosive coating according to claim 6, characterized in that: The preparation method of component B is as follows: deionized water, oligomer containing amino group, pH value adjuster, hydroxide or oxide, pigment filler, and additive are sequentially added into a container, dispersed or ground at high speed, and filtered and packaged after testing its fineness to be less than 50 microns.

Citation Information

Patent Citations

  • Inorganic phosphate compositions and methods

    CN102781871A

  • Water-based inorganic anticorrosive paint, anticorrosive coating and application thereof

    CN109943106A

  • Resin for improving flexibility of water-based nano-coating, and preparation method thereof

    CN110835396A

  • Coating solution for non-oriented silicon steel as well as preparation method and application of coating solution

    CN113831773A